First record of Alepia Enderlein (Diptera, Psychodidae) in Mexico, with the description of two new species - Durán-Luz, Juana; Ibáñez-Bernal, Sergio; Sandoval-Ruiz, César Antonio (Zootaxa, 2018)
Genus Alepia Enderlein is for the first time recorded in Mexico. Specimens were captured in southern Puebla at the central area of Mexico corresponding to two new species which are described with male and female characteristics. One species belongs to the group of species characterized by a compact group of accessory retinacula originated on a dark area of surtyli, having the eye bridge ending in a small number of facet rows, and the other to the group of species characterized by the accessory retinacula scattered, absence of dark area on the surtyli, and a broad eye bridge with three facet rows.